Pengaruh pertumbuhan ekonomi, pendidikan dan kesehatan terhadap tingkat kemiskinan di Kota Jambi Periode 2004-2017 - Pepi Putriani; Junaidi Junaidi; Jaya Kusuma Edi (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2018)
The purpose of this study was to determine the effect of economic growth, education and health on the level of poverty levels in Jambi City. The type of data used in this stufy is secondary data sourced from Jambi, in the form of time series data. The method in this study is a quantitative analysis method. The analytical tool used is multiple linier regression. The results ofthe study with a significant level of 5%, the GDP variable is obtained at a significant level of 0,781 with a significant value greater than 0,05, this means that the average length of school affects the level of poverty and the expectancy variable obtained a significant level of 0,01 with a value significanty smaller than 0,05, which means that life expectancies affect the poverty level.